KOMUNIKASI GURU PENDIDIKAN AGAMA DALAM MEMBENTUK KARAKTER SISWA - Heri Rahmatsyah Putra; Fadhlur Rahman Armi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
Abstract Character is an important capital in human life. Character is formed in the family and school environment. Schools as institutions for gaining knowledge and finding identity for students are determined by the communication skills of religious education teachers in influencing and providing instruction and good examples to students. This research was conducted using the field research method through a qualitative approach. The results of the study indicate that religious education teachers have provided understanding and influence on the formation of students' character through the important role of teachers and the ability of teachers to manage interactions in learning activities through good communication to develop positive attitudes through inculcating Islamic values ​​so that students can grow a sense of trust. self. Through the ability of teachers to be open, sensitive, responsive, friendly and patient to students in learning. As well as with the ability of teachers to develop a positive attitude in learning activities. Keyword: Communication, Teacher of Religion, Character